Severe anemia caused by babesiosis in a maned wolf (Chrysocyon brachyurus) - Phair, Kristen A.; Carpenter, James W.; Smee, Nicole; Myers, Carl B.; Pohlman, Lisa M. (My University, 2013)
An 8-yr-old, captive, spayed, female maned wolf (Chrysocyon brachyurus) developed progressive lethargy and weakness over a 24-hr period. Clinical signs included vomiting, recumbency, horizontal nystagmus, possible blindness, pale icteric mucus membranes, and port-wine colored urine. A complete blood cell count revealed severe anemia (packed cell volume [PCV], 6%) and intraerythrocytic piroplasms consistent with a Babesia species. Polymerase chain reaction testing later confirmed babesiosis. The wolf was treated with imidocarb dipropionate, antibiotics, and fluid therapy. A whole-blood transfusion from a sibling maned wolf also was performed. Despite aggressive treatment, the wolf failed to improve and was euthanized. To the authors’ knowledge, this is the first documented case of babesiosis in a captive maned wolf in North America. Surveillance of infectious diseases in captive and wild maned wolf populations should be expanded to include screening for Babesia species. Tick control also should be implemented to prevent and decrease transmission of the disease to this endangered species.
Keywords: Anemia; Babesia; Chrysocyon brachyurus; Maned wolf